Counteracting with healing antidotes. Beyond Kelsen, towards Ross - SERPE, Alessandro (Utopía y Praxis Latinoamericana, 2016)
My aim in this essay is not to compare theÂ thoughts of Norberto Bobbio and Alf Ross on allÂ matters. Instead, I intend to examine some key areasÂ of their legal philosophy in which one can reasonablyÂ see Bobbio as responding to or influenced by Ross,Â or in which comparisons between their theories areÂ particularly interesting. The comparison is especiallyÂ purposeful with regard to Bobbio”™s sixties works whereÂ Kelsenism, along with all attempts to ground law in aÂ presupposed grundnorm and of purifying legal science Â fail in his view. Particularly, the need for scientific clarity Â and adherence to reality by appealing to the basic tenetsÂ of analytical philosophy and logical empiricism displayÂ levels of approval for Ross. Although Kelsenian legalÂ positivism has continued to figure in Bobbio”™s legalÂ thought long after he rejected Kelsen”™s purity thesis,Â Bobbio”™s devoted discussions on legal positivism andÂ the doctrine of natural law, his later studies on legalÂ norms and on the interplay between law and force, mayÂ be seen as some of the more significant ways in whichÂ he integrates valuable insights of Ross”™ standpoints intoÂ his own theory.